Investigation of Antioxidant Activity of Gallic, Protocatechuic and Vanilic Acid using the Briggs-Rauscher Reaction as Tool - Gojak-Salimović, Sabina; Alijagić, Nedžmina; Ramić, Sabrina (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2023)
Hydroxybenzoic acids are an important class of polyphenols because their strong antioxidative activity. In this study, the antioxidant activity of three hydroxybenzoic acids was investigated using the Briggs-Rauscher reaction. Besides individual gallic, protocatechuic, and vanillic acids at concentrations of 250, 500, and 1000 µM respectively, the various mixtures of two and three hydroxybenzoic acids were also tested. The highest antioxidant activity showed protocatechuic acid at a concentration of 1000 µM while the lowest antioxidant activity was observed for vanillic acid at a concentration of 250 µM. The most of investigated hydroxybenzoic acids mixtures showed some degree of antagonistic effect. The highest antagonistic effect was found for the equimolar mixture of protocatechuic and vanillic acid at concentration of 250 μM. On the contrary, the equimolar mixture of gallic acid and vanillic acid at the same concentration indicated a high synergistic effect.